Pengaruh Proper Rating, Industrial Type, dan Komite Audit terhadap Carbon Emission Disclosure: - Suminar, Suminar; Yuliandhari, Willy Sri (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
Climate change is the impact of global warming which has a negative impact on daily human activities. The negative impacts of climate change are increasing sea surface temperatures, changes in rainfall, extreme weather intensity and high waves. Pollution of carbon pollution is one of the problems that exist in environmental accounting. Through disclosure of carbon emissions, stakeholders can measure the company's role in reducing greenhouse gas (GHG) emissions and also indicate that the company cares about the environment. The purpose of this study is to determine the simultaneous and partial effects of PROPER Rating, Industrial Type, and Audit Committee influence on Carbon Emission Disclosure. The objects used as samples in this study are non-financial companies listed on the Indonesia Stock Exchange for the 2018-2021 period. The technique used in this study was purposive sampling with a total sample of 23 samples from 509 companies. The data analysis model used in this study is multiple linear regression analysis. This study gives the result that the PROPER Rating, Industrial Type, and Audit Committee variables simultaneously influence Disclosure of Carbon Emissions Keywords: Carbon Emission Disclosure, PROPER Rating, Industrial Type, and Committee Audit